Inscrição subjetiva como alicerce da autoria: produções textuais de crianças a partir de leitura de cordéis - Mélo, érica Maria Silva Montenegro de (2010)
This work is the result of a research linked to the Project Subject from the Unconscious, Discourse and Social Insertion in Situations of Acquisition and Language Disturbs, obeying, this way, to the criteria and rules adopted by it. Writing involves the subject in infinite actions, among them some will demand from him/her more than his/her consciousness can give, more than all his/her learning can demand and more abilities or competences that he/she can dominate. That is the reason why school has been on the stage where the writing, dismissed from authorship, has been criticized by the teachers who are trying to stop the copies. This bad procedure happens, many times, even when the school reflects the modifications of modern life, with all its facilities, in these are included many discussions around the children authorship in their textual and research productions. Although the school resistance, this writing fulfilled with elements that look like more a bad faking copy or retelling from other texts is opening space among young ―writers‖. Writing, in its essence, implies making distance from the copy and implies, in a way that allows to the reader noticing who is the subject there, writing the text, and not copying the other s quote. This study, then, consists in a result of a collection of textual productions from children in written language acquisition process, that were made from the reading of cordel leaflets done to children. Analysis was made, taking as reference some concepts of psychoanalytic theory, specially, in the reading of Freud works, Lacan and teacher Claudia de Lemos, particularly in the phase that was linked to the psycholinguistic camp. This theoretical camp allowed us to link the conception of langue and parole as an unconsciousness subject crossing. These studies were useful to make possible the identification of subjective inscription elements from the children in their texts, and to think about their mistakes, directing the look to notice the singularity that is installed in their productions, making us far from the explanation of these mistakes and making us close from the questioning. This way, the singularity of the children s textual production shows its importance to the review of the mistakes like an evidence of subject s language movements, as something constitutive and indicative of singularity, as a consequence, the textual productions would allow us to identify the evidences of authorship. We noticed that, the subjective inscription is in the children text like an authorship mark, based on the subject subjectification, even in those that are in their first steps in language acquisition. That question is constituted by an evidence of authorship mark that the little writers has been tracking since the earlier times, above all, because it results in his/her writing. This path was chosen with the intention that the teachers give special attention to the authorship like student s inscription in the texts that they produce